A pilot study of autologous tumor lysate-loaded dendritic cell vaccination combined with sunitinib for metastatic renal cell carcinoma. Issue 1 (19th August 2014) - Matsushita, Hirokazu; Enomoto, Yutaka; Kume, Haruki; Nakagawa, Tohru; Fukuhara, Hiroshi; Suzuki, Motofumi; Fujimura, Tetsuya; Homma, Yukio; Kakimi, Kazuhiro
Abstract : Background: Sunitinib, a tyrosine kinase inhibitor currently in use for the treatment of metastatic renal cell carcinoma (mRCC), has been reported to modulate immunosuppressive cells such as myeloid-derived suppressor cells (MDSCs) and regulatory T cells (Tregs) in addition to exerting anti-angiogenic effects. We conducted a clinical trial of dendritic cell (DC)-based immunotherapy together with sunitinib in mRCC patients in an effort to enhance immunotherapeutic efficacy by inhibiting immunosuppressive cells. Methods: Patients aged ≥20 years with advanced or recurrent mRCC who underwent nephrectomy were eligible for this study. Autologous tumor samples were obtained by surgery under aseptic conditions and used for preparing autologous tumor lysate. About 4 weeks after surgery, leukapheresis was performed to isolate peripheral blood mononuclear cells (PBMCs). DCs were generated from adherent PBMCs in the presence of recombinant human granulocyte macrophage colony-stimulating factor (GM-CSF) (500 IU/ml) and recombinant human IL-4 (500 IU/ml). Autologous tumor lysate was loaded into mature DC by electroporation. Eight patients were enrolled in the study and received sunitinib at a dose of 50 mg p.o. daily for 28 days followed by 14 days of rest. Tumor lysate-loaded DCs were administered subcutaneously every two weeks, with concomitant sunitinib. Results: No severe adverse events related to vaccination were observed. Sunitinib decreased the frequencies of MDSCs in peripheral blood of 5 patients and of Tregs in 3. Tumor lysate-reactive CD4 or CD8 T cell responses were observed in 5 patients, 4 of whom showed decreased frequencies of Tregs and/or MDSCs. The remaining 3 patients who failed to develop tumor-reactive T cell responses had high levels of IL-8 in their sera and did not show consistent reductions in MDSCs and Tregs. Conclusions: DC-based immunotherapy combined with sunitinib is safe and feasible for patients with mRCC. Trial registration: UMIN000002136